Brain Development Methods and Protocols - Sprecher, Simon G.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2014)
Providing widely used techniques in genetic model systems and many complementing animal models, Brain Development: Methods and Protocols focuses its expert contributions on two key technical aspects of developmental neurobiology: detection of gene expression and functional characterization of developmental control genes.  Covering animal models such as the fruit fly, zebra fish, chicken, and mouse, this detailed book views in situ hybridization, reporter gene expression, and immunohistochemical staining methods, as well as RNA interference, Morpholino, or transgenic techniques through the prism of these models.  Written in the highly successful Methods in Molecular Biology series format, chapter include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Practical and cutting-edge, Brain Development: Methods and Protocols aims to provide precise technical protocols but also allows for comparing a wide range of protocols in different tissues and species.
Immunostaining of the Developing Embryonic and Larval Drosophila Brain -- Non-Fluorescent RNA In Situ-Hybridization Combined with Antibody Staining to Visualize Multiple Gene Expression Patterns in the Embryonic Brain of Drosophila -- Analysis of Complete Neuroblast Cell Lineages in the Drosophila Embryonic Brain via DiI-Labeling -- Flybow to Dissect Circuit Assembly in the Drosophila Brain -- Immunofluorescent Labeling of Neural Stem Cells in the Drosophila Optic Lobe -- Using MARCM to Study Drosophila Brain Development -- Dye Coupling and Immunostaining of Astrocyte-Like Glia Following Intracellular Injection of Fluorochromes in Brain Slices of the Grasshopper, Schistocerca gregaria -- Methods in Brain Development of Molluscs -- In Situ Hybridization and Immunostaining of Xenopus Brain -- Microinjection Manipulations in the Elucidation of Xenopus Brain Development -- Morpholino Studies in Xenopus Brain Development -- Sensitive Whole-Mount Fluorescent In Situ Hybridization in Zebrafish Using Enhanced Tyramide Signal Amplification -- Dynamic Neuroanatomy at Subcellular Resolution in the Zebrafish -- Anatomical Dissection of Zebrafish Brain Development -- Immunohistochemistry and In Situ Hybridization in the Developing Chicken Brain -- Transplantation of Neural Tissue: Quail-Chick Chimeras -- RNAi-Based Gene Silencing in Chicken Brain Development -- Immunohistochemistry and RNA In Situ Hybridization in Mouse Brain Development -- In Utero Electroporation to Study Mouse Brain Development -- The Cre/Lox System to Assess the Development of the Mouse Brain.
Keywords: Neurosciences; Neurobiology; Neurosciences; Neurobiology